Chemoresistance is associated with overexpression of HAX-1, inhibition of which resensitizes drug-resistant breast cancer cells to chemotherapy - Ji Yang; Yue Wu; Xiao Wang; Liqian Xu; Xiaohong Zhao; Yunmei Yang (Tumor Biology)
Acquired resistance to standard chemotherapy is the common and critical limitation for cancer therapy. Hematopoietic cell-specific protein 1-associated protein X-1 (HAX-1) has been reported to be upregulated in numerous cancers. However, the role of HAX-1 in oncotherapy remains unclear. In this study, we established MDA-MB-231 cell lines which were resistant to cisplatin (MDA-MB-231/CR) or doxorubicin (MDA-MB-231/DR) to study the chemoresistance in breast cancer. As a result, the HAX-1 which is an apoptosis-associated protein was observed to be overexpressed in both MDA-MB-231/CR and MDA-MB-231/DR compared with the routine MDA-MB-231 cells. Moreover, knockdown of HAX-1 via RNA interference decreased IC50 level of cisplatin by 70.91% in MDA-MB-231/CR cells, and the IC50 level of doxorubicin was decreased by 76.46% in MDA-MB-231/DR cells when the HAX-1 was downregulated. Additionally, we found that the knockdown of HAX-1 induced the release of cytochrome C from mitochondria, resulting in the activation of caspases. Taken together, our study indicates that the overexpression of HAX-1 is essential in the development of chemoresistance in breast cancer. Furthermore, we identify that HAX-1 may become the target for cancer therapy.